2015
DOI: 10.3791/52287
|View full text |Cite
|
Sign up to set email alerts
|

Signal Attenuation as a Rat Model of Obsessive Compulsive Disorder

Abstract: In the signal attenuation rat model of obsessive-compulsive disorder (OCD), lever-pressing for food is followed by the presentation of a compound stimulus which serves as a feedback cue. This feedback is later attenuated by repeated presentations of the stimulus without food (without the rat emitting the lever-press response). In the next stage, lever-pressing is assessed under extinction conditions (i.e., no food is delivered). At this stage rats display two types of lever-presses, those that are followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
2
0
1
Order By: Relevance
“…Signal attenuation is a model of OCD in which the rat excessively presses the lever not to collect the reward after signal-attenuation training [60]. This behavior is similar to the unusual repetitive behavior of OCD patients.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Signal attenuation is a model of OCD in which the rat excessively presses the lever not to collect the reward after signal-attenuation training [60]. This behavior is similar to the unusual repetitive behavior of OCD patients.…”
Section: Discussionmentioning
confidence: 93%
“…The number of completed excessive-lever-press trials were observed and recorded. The obsessive-compulsiveinduced experimental rats showed more repeated trials than the normal and treated groups [60].…”
Section: Signal-attenuation Modelmentioning
confidence: 85%
“…As maiores descobertas sobre a circuitaria envolvida são decorrentes de trabalhos de neuroimagem funcional, nos quais pesquisadores observaram um possível vínculo entre manifestações clínicas do TOC e mudanças na atividade no circuito córtico-estriado-tálamocortical (CETC) (GRAYBIEL, RAUCH, 2000;ULLRICH et al, 2018) associado aos neurotransmissores glutamato e ácido gama-aminobutírico (GABA). Outros estudos indicam a participação de neurotransmissores como a serotonina (5-hidroxitriptamina -5-HT) e a dopamina (DA) (CORDIOLI, 2014), além do envolvimento de hormônios ovarianos (estrógeno e progesterona) (MITRA et al, 2016), apontados como moduladores do TOC por provocarem ou intensificarem os sintomas em mulheres (GOLTSEKER et al, 2015).…”
Section: 1transtorno Obsessivo Compulsivounclassified